2010
DOI: 10.1007/978-3-642-17514-5_38
|View full text |Cite
|
Sign up to set email alerts
|

π/2-Angle Yao Graphs Are Spanners

Abstract: We show that the Yao graph Y 4 in the L 2 metric is a spanner with stretch factor 8(29+23 √ 2). Enroute to this, we also show that the Yao graph Y ∞ 4 in the L ∞ metric is a planar spanner with stretch factor 8.In the appendix, we improve the stretch factor and show that, in fact, Y k is a spanner for any k ≥ 7. Recently, Molla [4] showed that Y 2 and Y 3 are not

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 4 publications
0
27
0
Order By: Relevance
“…Very little is known for k 6. For instance, it was known that Y 4 -graphs are connected [16] and recently it has been shown that they are 8(29 + 23 √ 2)-spanners 4 [4]. A very recent result [29] states that Y 6 -graphs are 20.4-spanners.…”
Section: Theta-graphsmentioning
confidence: 99%
“…Very little is known for k 6. For instance, it was known that Y 4 -graphs are connected [16] and recently it has been shown that they are 8(29 + 23 √ 2)-spanners 4 [4]. A very recent result [29] states that Y 6 -graphs are 20.4-spanners.…”
Section: Theta-graphsmentioning
confidence: 99%
“…Notice that the Yao ∞ 4 (P ) graph is a subgraph of the L ∞ Delaunay graph on P . The Yao ∞ 4 (P ) was shown to be an 8 √ 2-spanner [12].…”
Section: Variants Of Delaunay Graphsmentioning
confidence: 99%
“…Due to space restrictions, some of these properties are stated without proofs. The proofs can be found in [1]. The ultimate goal of this section is to show that, if two edges in Y 4 cross, there is a short path between their endpoints (Lemma 8).…”
Section: Y 4 In the L 2 Metricmentioning
confidence: 99%
“…Proof. For the sake of clarity, we only prove here that there is a short path p(a, b) between a and b, and skip the calculations of the actual stretch factor t (which are detailed in the appendix of [1]). We refer to an edge or a path as short if its length is within a constant factor of |ab|.…”
Section: S1mentioning
confidence: 99%
See 1 more Smart Citation